Dec2 attenuates autophagy in inflamed periodontal tissues - Shunichi Oka; Xiaoyan Li; Fuyuki Sato; Fengzhu Zhang; Nitesh Tewari; Chongchong Chen; Liangjun Zhong; Makoto Makishima; Yi Liu; Ujjal K. Bhawal (Immunity, Inflammation and Disease)
Abstract Introduction Transcriptional regulation of autophagy depends on the transcription factors coordinated inflammatory feedback mechanism. Here, we provide a comprehensive functional characterization of periodontal ligament fibroblasts (PDLFs) treated with Porphyromonas gingivalis lipopolysaccharide (LPS), aiming to reveal previously unappreciated biological changes and to investigate how a transcription factor differentiated embryonic chondrocytes 2 (Dec2)‐deficient environment influences the function of autophagy in nflamed human PDLFs. Methods A Dec2‐deficient (Dec2KO) experimental periodontal inflammation mouse model and treatment with P. gingivalis LPS were employed to examine the role of autophagy in PDLFs using hematoxylin and eosin staining and immunohistochemistry in vivo. A Dec2 small interfering RNA (siRNA) was used to modulate autophagy, and the effect of autophagy on the Dec2 pathway was explored using real‐time polymerase chain reaction and western blot analysis in vitro. Results LPS‐treated human PDLFs (HPDLFs) induced autophagy, as demonstrated by the enhanced levels of microtubule‐associated protein 1 light chain 3‐II (LC3‐II) and the induction of ATG5, Beclin1, and Dec2. Compared with a scrambled siRNA, a Dec2 siRNA triggered the detrimental influences of LPS and markedly enhanced autophagy expression in inflamed HPDLFs. The expression of phosphorylated ERK was increased and levels of phosphorylated mammalian target of rapamycin (mTOR) were decreased after exposure to LPS in Dec2 siRNA transfected HPDLFs. The Dec2KO model exhibited that P. gingivalis in Dec2 deficient conditions increases the inflammation of PDLFs by regulating autophagy. Conclusions These results demonstrate that a Dec2 deficiency can alleviate LPS‐induced inflammation via the ERK/mTOR signaling pathway by regulating autophagy, conceivably delivering a novel approach for the detection of periodontal treatments.